2013
DOI: 10.1038/pr.2013.16
|View full text |Cite
|
Sign up to set email alerts
|

β1-Adrenoceptor mRNA level reveals distinctions between infantile hemangioma and vascular malformations

Abstract: Background: Infantile hemangioma (Ih) is the most frequent vascular tumor of early childhood. Recently, propranolol, a nonselective β 1 -and β 2 -adrenoceptor inhibitor, was introduced into the therapy of severe proliferating Ih with excellent results. however, the underlying mechanism of action of propranolol is still unclear. Methods: We performed immunohistochemistry for cluster of differentiation 31 (cD31), D2-40, glucose transporter-1 (GLUT-1), and Ki67 in order to characterize 21 vascular anomalies (nine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 12 publications
(10 reference statements)
0
15
0
Order By: Relevance
“…In the involuting phase, reduction of the vascular lesions occurs; diseased vessel undergoes vasoconstriction leading to a slow progressive regression. Propanolol, a non-selective inhibitor of ß(1)- and ß(2)-adrenoceptor, is known to show a good therapeutic effect [8], [9], likely due, at least in part, to its ability to induce such vasoconstriction. In small babies vessel reduction occurring during the IH involuting phase may give a significant reduction of the vascular bed, relevant as compared to the body mass, with a consequent blood-concentration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the involuting phase, reduction of the vascular lesions occurs; diseased vessel undergoes vasoconstriction leading to a slow progressive regression. Propanolol, a non-selective inhibitor of ß(1)- and ß(2)-adrenoceptor, is known to show a good therapeutic effect [8], [9], likely due, at least in part, to its ability to induce such vasoconstriction. In small babies vessel reduction occurring during the IH involuting phase may give a significant reduction of the vascular bed, relevant as compared to the body mass, with a consequent blood-concentration.…”
Section: Discussionmentioning
confidence: 99%
“…IH arises from multipotent stem cells leading to endothelial cells in the proliferating phase and to adipocytes during the involution/involuted phase and molecular mechanisms underlying hemangioma onset and involution are only partially defined [8]. Messenger RNA level of β-adrenoceptor has been indicated as possibly involved and such level may represent a potential molecular marker useful to discriminate IH from other vascular malformations [9]. Furthermore, Glucose transporter-1 (Glut-1) may also represent an useful diagnostic marker [10].…”
Section: Introductionmentioning
confidence: 99%
“…4,10,12,13,14,15 Recently, we have shown that propranolol also affects HemSCs, causing accelerated adipogenesis. In the absence of adipogenic induction, propranolol increased proadipogenic gene expression in HemSCs as early as 24 hours after starting treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Agonists and antagonists of β-ARs are known to act antithetically via the same intracellular pathways [92]. Given that the expression of all three β-ARs has been demonstrated in IH tumors [93][94][95][96], does β-adrenergic signaling play a role in the pathogenesis of IH? This hypothesis was immediately and, to some degree, indirectly testable by Mayer et al [97], who found that intrauterine exposure to β 2 -sympathomimetic hexoprenaline can increase the occurrence of IH in preterm infants, suggesting a role for β-AR stimulation in the initiation of IH.…”
Section: β-Adrenergic Signalingmentioning
confidence: 99%